The Influence of Basketball on the Asymmetry in the Use of Limbs - Aleksandar Čvorović (Montenegrin Sports Academy, 2012)
The purpose of this study was to determine how basketball affects the uneven use of the limbs in relation to non-basketball population. Participants were compared by multiple motoric and situational tests, and for each participant tested the relationship between all limbs, both upper and lower. Before the motoric and situational tests participants completed a questionnaire on preference in limb use in everyday life and during sports activities. Participants belong to two groups, one group of young players with the rank of at least four years experience in basketball training, while the second group consists of members of the healthy school population, but with no experience in the continuous training of basketball. The study tested the explosive power of the lower and upper limbs, and the reaction time and agility in the lower limbs. Statistical analysis of results showed significant differences in certain tests between groups and within groups, both among the upper and lower extremities. It can be concluded that basketball as a specific sporting activity has positive influence on the development of the tested variables, while the level of asymmetry at basketball player is less than in the non-basketball population.